Healthcare system efficiency and its drivers in pre- and COVID-19 pandemic settings - Vishniakov, Dmitry; Kasiev, Naken; Abdrasulova, Fatima (Business, Management and Economics Engineering, 2023)
Purpose – The aim of the study is to assess healthcare system efficiency in both regular circumstances and during the COVID-19 pandemic, with a focus on key factors influencing efficiency, and offer health authorities insights into healthcare system resilience.Research methodology – The analysis was conducted in two stages. The initial stage involved the application of Data Envelopment Analysis output-oriented model with a constant-returnto-scale framework. The second stage employed Tobit regression method to identify factors that influenced countries’ efficiency.Findings – We identified the healthcare system efficiency of 14 CIS and EU countries in Pre and pandemic settings and provided a methodology for results interpretation accounting for the complexity of healthcare systems and temporal variations in pandemic trends. The Tobit regression highlighted the role of the health workforce, emphasizing the caution for the reduction of physicians in the system.Research limitations – The research focused on efficiency in just two regions of Eurasia and only considered medical factors as the primary drivers of efficiency. Additionally, the examination covered the initial year of the pandemic, reflecting only the earlier stages of countries’ performance during the pandemic.Practical implications – This study contributes to the assessment of healthcare resilience on a global scale and provides information for policymakers, aiding in the selection of optimal practices during the pandemic and enhancing preparedness for future crises.Originality/Value – Countries’ efficiency assessment in four models and two settings provides valuable insight into the healthcare systems’ resilience.